Diminished Health Returns of Educational Attainment Among Immigrant Adults in the United States - Assari, Shervin; Cobb, Sharon; Cuevas, Adolfo G.; Bazargan, Mohsen (Frontiers in Psychiatry, 2020)
Objectives. Marginalization-related Diminished Returns (MDRs) refer to weaker health effects of educational attainment for socially marginalized groups compared to the socially privileged groups. Most of the existing literature on MDRs, however, has focused on marginalization due to race, ethnicity, and sexual orientation. Thus, very limited information exists on MDRs of educational attainment among immigrant populations in the United States. Aims. Building on the MDRs framework and using a nationally representative sample of US adults, we compared immigrants and non-immigrants for the effects of educational attainment on psychological distress, self-rated health (SRH), and chronic diseases (CDs). Methods. The 2015 National Health Interview Survey (NHIS) has enrolled 33672 individuals who were either immigrants (n=6225; 18.5%) or non-immigrants (n=27429; 81.5%). The independent variable (IV) was the educational attainment that was treated as a categorical variable. The dependent variables included psychological distress, SRH, and CDs, all dichotomous variables. Age, gender, race, ethnicity, and region were confounders. Immigration (nativity status) was the moderator. Results. Higher educational attainment was associated with lower odds of psychological distress, poor SRH, and CDs. However, immigration showed a significant statistical interaction with college graduation on all outcomes, which were suggestive of smaller protective effects of college graduation on psychological distress, poor SRH, and CDs for immigrants than non-immigrants. Conclusions. In line with MDRs, the associations between educational attainment and psychological distress, SRH, and CDs in the US are all weaker for immigrants than non-immigrants. To prevent health disparities, it is essential to decompose health inequalities that are due to low educational attainment from those that are due to diminished returns of educational attainment (i.e., MDRs). There is a need to help highly immigrants secure health outcomes, similar to non-immigrants. Such changes may require bold and innovative economic, public, and social policies that help immigrants to more effectively mobilize their educational attainment to secure tangible outcomes. Elimination of health disparities requires efforts that go beyond equalizing access to education.